2008
DOI: 10.1152/ajpregu.00611.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hindbrain melanin-concentrating hormone and neuropeptide Y administration on licking for water, saccharin, and sucrose solutions

Abstract: Melanin-concentrating hormone (MCH) and neuropeptide Y (NPY) are orexigenic peptides found in hypothalamic neurons that project throughout the forebrain and hindbrain. The effects of fourth ventricle (4V) infusions of NPY (5 microg) and MCH (5 microg) on licking for water, 4 mM saccharin, and sucrose (0.1 and 1.0 M) solutions were compared to identify the contributions of each peptide to hindbrain-stimulated feeding. NPY increased mean meal size only for the sucrose solutions, suggesting that caloric feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…More importantly, prepro-MCH mRNA was completely undetectable in the mouse nodose ganglion, even in the fasted condition. The absence of MCH in vagal afferents is consistent with the fact that the administration of MCH in the fourth ventricle does not influence food intake (Zheng et al, 2005; Baird et al, 2008). Even though differences in age, strain, bleeds of antibody, and diets may have influenced our results, we are confident that MCH is not produced by the vagal afferents.…”
Section: Discussionsupporting
confidence: 75%
“…More importantly, prepro-MCH mRNA was completely undetectable in the mouse nodose ganglion, even in the fasted condition. The absence of MCH in vagal afferents is consistent with the fact that the administration of MCH in the fourth ventricle does not influence food intake (Zheng et al, 2005; Baird et al, 2008). Even though differences in age, strain, bleeds of antibody, and diets may have influenced our results, we are confident that MCH is not produced by the vagal afferents.…”
Section: Discussionsupporting
confidence: 75%
“…Baird et al (2009) suggested that ICV injection of orexin-A did not affect orosensory evaluation for sucrose solution in rats because the early ingestion rate or lick burst size increased as sucrose concentration was increased from water to 100 mM and 1 M sucrose; however, administration of orexin-A did not alter those measures. The authors also reported that ICV injection of neuropeptide Y increased sucrose solution intake without affecting taste evaluation (Baird et al 2008). Conversely, melanin-concentrating hormone enhanced taste evaluation (Baird et al 2006), and orexin is likely to modulate the sensitivity of peripheral olfactory processing (Apelbaum et al 2005;Hardy et al 2005) and increase olfactory sensitivity (Julliard et al 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the identification of neuropeptides that regulate orexigenic and anorexigenic components of feeding provides an opportunity to examine the molecular basis of food intake. Several studies suggest a distinct role for neuropeptides in licking microstructure and ingestive behavior (Aja, Schwartz, Kuhar, & Moran, 2001; Baird et al, 2006, 2008; Zukerman et al, 2009). Combined with the use of mouse genetics and pharmacological studies, microstructural analyses will surely be useful for elucidating the etiology of food intake and associated disorders.…”
Section: Discussionmentioning
confidence: 99%